FOREIGN DIRECT INVESTMENT AND SUSTAINABLE HUMAN CAPITAL DEVELOPMENT: A BIBLIOMETRIC ANALYSIS APPROACH - Kamsin, Khairunisah; Alin, James; Kogid, Mori; Madli, Faerozh; Kristina, Anita (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
The growing discourse on the role of Foreign Direct Investment (FDI) in promoting sustainable human capital development has attracted significant scholarly attention, yet there remains a lack of systematic mapping of research patterns in this domain. This study addresses this gap by conducting a bibliometric analysis to examine global research trends, thematic structures, and collaboration networks on FDI and sustainable human capital development. Using the Scopus database, we applied an advanced search strategy, which retrieved a total of 385 documents published between 2021 and 2025. The data were first cleaned and harmonized using OpenRefine to ensure consistency and reliability, after which the Scopus Analyzer was employed to generate descriptive statistics and publication trends across years, countries, and subject areas. VOSviewer software was then used to construct and visualize co-occurrence networks of author keywords, citation relationships, and international collaborations. The analysis revealed a notable increase in publications during 2023–2025, reflecting growing scholarly and policy interest in aligning investment flows with sustainable human capital outcomes. Economics, Social Sciences, and Environmental Studies emerged as the dominant subject areas, indicating the multidimensional nature of this research field. Co-occurrence mapping identified four main clusters centered around FDI, human capital, economic growth, and sustainable development, highlighting the thematic interconnectedness between investment policies, labor productivity, and long-term development goals. China, the United States, and Malaysia were among the most influential contributors in terms of both output and citation impact, suggesting strong research leadership in both developed and emerging economies. Overall, this study not only provides a comprehensive overview of the intellectual structure and global collaboration in this field but also contributes to the body of knowledge by identifying emerging themes and gaps for future research on the nexus between FDI and sustainable human capital development.